2018
DOI: 10.1093/femspd/fty075
|View full text |Cite
|
Sign up to set email alerts
|

The Type I Interferon Receptor is Not Required for Protection in the Chlamydia and HSV-2 Murine Super-infection Model

Abstract: Chlamydia trachomatis/HSV-2 vaginal co-infections are seen clinically, suggesting that these sexually transmitted pathogens may interact. We previously established an intravaginal Chlamydia muridarum/HSV-2 super-infection model and observed that chlamydial pre-infection protects mice from a subsequent lethal HSV-2 challenge. However, the mechanism of protection remains unknown. The type I interferon, IFN-β, binds to the type I interferon receptor (IFNR), elicits a host cellular antiviral response and inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Our U-tube experiments also demonstrated that its antiviral effect is unrelated to the host's immune system. Notably, Slade et al's study showed that the antiviral effect of Cm wiess strain against HSV-2 does not work by stimulating host secretion of IFN- [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our U-tube experiments also demonstrated that its antiviral effect is unrelated to the host's immune system. Notably, Slade et al's study showed that the antiviral effect of Cm wiess strain against HSV-2 does not work by stimulating host secretion of IFN- [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our results show that Chlamydia's antagonistic effect on related viruses is cell-autonomous. Slade et al's study suggests that the antiviral effect of Cm is density-dependent, requiring viable Cm (or its components) to exist in the early stages of infection in the host without relying on stimulating the host to secrete antiviral IFN- [14,15] . Previous studies on the antiviral mechanism of Wolbachia in the host has demonstrated that its antiviral effect is also cell-autonomous and relies on the distribution density of Wolbachia in the host.…”
Section: Discussionmentioning
confidence: 99%
“…Регуляторную функцию ИФН-β способен реализовывать через модуляцию TLR-зависимого иммунного ответа, запуская каскад противовирусных реакций. Это послужило формированию мнения, что изолированный дефицит данного звена интерфероновой системы не играет клинически значимой роли при инфекционном поражении [9]. Основываясь на результатах нашего исследования, можно сделать вывод, что, несмотря на большее изменение уровня ИФН-β в группе с ПВИ и хламидийной инфекцией, уровень ИФН-γ в данной группе изменялся в меньшей степени, что, безусловно, требует дальнейшего изучения с позиции перекрестных взаимодействий ИФН.…”
Section: Discussionunclassified